Diagnostic assessment of the experience and expression of anger in young university students – An approach to the prevention of risky behaviors - Ortiz Sánchez, Diana (2023)
According to Spielberg (1988), anger is defined as a basic emotion which occurs at a particular moment before aggression or hostility. State anger is characterized by subjective feelings that vary in intensity, from mild irritation or annoyance to intense fury and rage. On the other hand, trait anger is defined as a willingness to perceive a wide range of situations as annoying or frustrating and to experience increased state anger. The experience of anger has been related to different health problems (Averill 1983, Mytton et al. 2002), personality disorders (DiGiussepe et al. 2012), suicide risk (Hawkins et al. 2014), and others. The purpose of this study was to conduct a diagnostic assessment of the experience and expression of anger in young university students, as a first step toward future actions promoting proper regulation and anger management. For this purpose, an ex post facto cross-sectional study was carried out in a university student population by using the State-Trait Anger Expression Inventory (STAXI-2) (Miguel-Tobal et al. 2009). Appropriate anger management is considered a psychological resource; considering this and the results obtained, it is possible that the difficulty in expressing and properly perceiving the experience of anger may predominate in the population assessed. This suggests that these individuals show a tendency towards inhibition and the display of avoidance or denial mechanisms, which can be considered a risk factor for the development of health problems.